2017
DOI: 10.1136/tsaco-2017-000120
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Trauma in Western Massachusetts: Fact or Folklore?

Abstract: BackgroundPrevious studies have demonstrated a significant relationship between weather or seasons and total trauma admissions. We hypothesized that specific mechanisms such as penetrating trauma, motor vehicle crashes, and motorcycle crashes (MCCs) occur more commonly during the summer, while more falls and suicide attempts during winter.MethodsA retrospective review of trauma admissions to a single Level I trauma center in Springfield, Massachusetts from 01/2010 through 12/2015 was performed. Basic demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
3
23
1
Order By: Relevance
“…This may be related to the lack of opportunity to engage in activities usually associated with injury, such as; excessive consumption of alcohol, interpersonal violence and RTCs [ 22 , 23 ]. The scale of change, by as much as 68% reduction in the early phase of the lockdown, is unprecedented and differed significantly from the seasonal variations (which ranges from 10 to 20%) previously reported [ 5 7 ]. Profound differences in the demographics of the two matched periods were observed.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This may be related to the lack of opportunity to engage in activities usually associated with injury, such as; excessive consumption of alcohol, interpersonal violence and RTCs [ 22 , 23 ]. The scale of change, by as much as 68% reduction in the early phase of the lockdown, is unprecedented and differed significantly from the seasonal variations (which ranges from 10 to 20%) previously reported [ 5 7 ]. Profound differences in the demographics of the two matched periods were observed.…”
Section: Discussioncontrasting
confidence: 57%
“…[22,23]. The scale of change, by as much as 68% reduction in the early phase of the lockdown, is unprecedented and differed significantly from the seasonal variations (which ranges from 10 to 20%) previously reported [5][6][7]. Profound differences in the demographics of the two matched periods were observed.…”
Section: Discussionmentioning
confidence: 83%
“…As previously reported, trauma admissions show seasonal differences with a mid-year peak and the “trauma season” spanning from April to November [ 22 ]. Although falls and motor vehicle accidents were reported to be more frequent in the winter season [ 23 ], trauma numbers in March/April were comparable to those in February/March in ordinary years without a pandemic [ 24 ]. This allows the assumption that lower orthopedic trauma cases during the PRE compared to the CTRL period, may have been caused by people already being more cautious during the early months of the COVID-19 pandemic, although a shutdown was not yet in place.…”
Section: Discussionmentioning
confidence: 99%
“…However, more injuries were found in the months of July and August, which was described as Summer in the Northern Meteorological Seasons and Rainy Season in Bangladeshi Seasons. Earlier, a study from adult trauma cases in the USA described significant seasonal variations of mechanism of injury and reported that falls were significantly more during winter and RTAs were more during fall and winter than spring (Nahmias et al, 2017). The South Indian study reported that majority of injuries in children occurred during the most active part of the day (6 am-5 pm) and about half of their patients presented during the afternoon shift (3 pm-10 pm) (Paul et al, 2018).…”
Section: Discussionmentioning
confidence: 99%